2017
DOI: 10.1056/nejmoa1608664
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cardiovascular Disease in Type 1 and Type 2 Diabetes

Abstract: BACKGROUNDLong-term trends in excess risk of death and cardiovascular outcomes have not been extensively studied in persons with type 1 diabetes or type 2 diabetes. METHODSWe included patients registered in the Swedish National Diabetes Register from 1998 through 2012 and followed them through 2014. Trends in deaths and cardiovascular events were estimated with Cox regression and standardized incidence rates. For each patient, controls who were matched for age, sex, and county were randomly selected from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
725
8
46

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,058 publications
(804 citation statements)
references
References 39 publications
25
725
8
46
Order By: Relevance
“…Furthermore, large benefits are seen when multiple cardiovascular risk factors are addressed simultaneously. Under the current paradigm of aggressive risk factor modification in patients with diabetes, there is evidence that measures of 10-year coronary heart disease (CHD) risk among U.S. adults with diabetes have improved significantly over the past decade (1) and that ASCVD morbidity and mortality have decreased (2)(3)(4).…”
mentioning
confidence: 99%
“…Furthermore, large benefits are seen when multiple cardiovascular risk factors are addressed simultaneously. Under the current paradigm of aggressive risk factor modification in patients with diabetes, there is evidence that measures of 10-year coronary heart disease (CHD) risk among U.S. adults with diabetes have improved significantly over the past decade (1) and that ASCVD morbidity and mortality have decreased (2)(3)(4).…”
mentioning
confidence: 99%
“…1 A recent large Swedish registry study showed that although the incidence of CV events has declined substantially in subjects with diabetes between 1998 and 2014, it still remains significantly higher than in subjects without diabetes. 2 With the worldwide adult prevalence of diabetes rising from 4.7% in 1980 to 8.5% in 2014 the CV complications of diabetes represents a major public health challenge. 3 The increased CV risk associated with diabetes remains essentially the same when adjusting for conventional risk factors.…”
mentioning
confidence: 99%
“…[3] CV disease represents a high burden in patients with T2D, even if a progressive and sustained decline in major cardiovascular events (MACE) has been reported during the last two decades, both in the US [4] and in Sweden. [5] Nevertheless, fatal outcomes declined less among patients with T2D than among controls [5] and the excess risk in patients with T2D…”
Section: Introductionmentioning
confidence: 99%